THE INFLUENCE OF CAPITAL GEARING ON THE PERFORMANCE OF PRIVATE SECTOR BANKS IN INDIA: EVIDENCE BASED ON EVA, MVA AND SVA - N. Anchana; R. Azhagaiah (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the influence of capital gearing on the performance of Private Sector Banks in India. Based on performance measures, viz, Economic Value Added, Market Value Added, and Social Value Added of the Private Sector Banks in India, for a period of five years ranging from 2018-19 to 2022-23. The data for the study were collected from the annual reports of the respective banks and the Statistica database. The sample for the study consists of 15 Private Sector Banks listed on the National Stock Exchange (NSE), which are divided into two categories viz. ‘low capital gearing banks’ and ‘high capital gearing banks’. The study used correlation and regression to analyse the influence of capital gearing on the performance of the selected banks and the results show that there is a positive significant influence of ‘capital gearing’ on the performance of both ‘low capital gearing’ and ‘high capital gearing’ private sector banks. Further, analysis of variance (ANOVA) is performed to study the difference between financial performance of the two categories of banks with reference to the modern performance measure and the results showed that EVA and SVA are the best measures for evaluating the performance of low capital gearing banks as well as high capital gearing banks.